2022
DOI: 10.1002/smll.202202604
|View full text |Cite
|
Sign up to set email alerts
|

Radicals Scavenging MOFs Enabling Targeting Delivery of siRNA for Rheumatoid Arthritis Therapy

Abstract: cell immersion. The progress of RA causes obvious joint pain to patient, resulting in joint destruction, bone and cartilage damage, and ultimate joint disability. RA is still incurable, and current treatment drugs can only alleviate symptoms, such as disease-modifying anti-rheumatic drugs, non-steroidal anti-inflammatory drugs, glucocorticoids (GCs), and biological agents. [2] However, most of these drugs require long-term administration, which not only brings financial burden to patients but also causes a ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 60 publications
0
40
0
Order By: Relevance
“…Furthermore, after nanosystems finish the delivery task, the residual nanocarriers can also have a positive effect on the treatment of RA rather than waste. To this end, Zhou et al [ 9 , 10 ] prepared tannic acid-based MOF and folic acid-anchored silver nanoparticles. Both of these two nanosystems primarily deliver anti-rheumatic drugs to the joints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, after nanosystems finish the delivery task, the residual nanocarriers can also have a positive effect on the treatment of RA rather than waste. To this end, Zhou et al [ 9 , 10 ] prepared tannic acid-based MOF and folic acid-anchored silver nanoparticles. Both of these two nanosystems primarily deliver anti-rheumatic drugs to the joints.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages, which are involved in the body’s nonspecific immunity, produce related inflammatory factors such as IL-1, IL-6, and TNF-α. These cytokines will stimulate FLSs and further activate osteoclasts (OCs), leading to bone damage [ 9 – 11 ]. Reports have shown that receptor activator for nuclear factor-κ B ligand (RANKL) is indispensable in osteoclast differentiation and activation, and the number and activity of osteoclasts are key factors in bone destruction [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The obtained solutions were centrifuged, the precipitations of MCS NPs were resuspended in 10 μL DEPC-treated water, and the supernatants were collected for comparison. The samples were loaded onto the preheated 4% agarose gel by using a previous reported method [ 55 ]. Then, the electrophoresis experiment was performed at 180 V for 20 min, and the gel was stained with ethidium bromide solution for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Biocompatible iron (3) carboxylate MOFs as RNA nanocarriers increased cellular uptake and gene activity in vitro [ 188 ]. Bovine Serum Albumin (BSA)-decorated MOF/anti-TNF-α siRNA showed high therapeutic efficacy against rheumatoid arthritis in collagen-induced arthritis (CIA) mice model [ 189 ].…”
Section: Application Of Various Mnps For Nucleic Acid Deliverymentioning
confidence: 99%